2007
DOI: 10.1002/glia.20495
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor acts as an opponent of growth‐stimulatory factors in retinal glial–endothelial cell interactions

Abstract: Pigment epithelium-derived factor (PEDF), a glycoprotein with pleiotropic functions, is naturally occuring in the eye and considered as crucial to prevent pathological angiogenesis. Since retinal glial (Müller) cells produce PEDF, the authors have studied its impact on glial-endothelial cellular interactions. Bovine retinal endothelial cells were cultured in the presence of culture media originating from primary Müller cells, and endothelial proliferation as well as phosphorylation of the mitogen-activated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 58 publications
4
51
1
Order By: Relevance
“…Because the ERK1/2 cascade is known to induce survival in various cells (40), the molecular mechanisms that prevent such an effect in ECs treated with PEDF constructs are not clear but may be dependent on the decline of ERK1/2 phosphorylation before JNK1/2 and p38␣ reach their peak of activity. PEDF-induced ERK1/2 phosphorylation has been previously reported by us (18) and others that linked it to the cytoprotective properties of PEDF (41,42). Indeed, our previous report showed that WT-PEDF and EEE-PEDF exhibit the same degree of neurotrophic and neuroprotective activity (18).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Because the ERK1/2 cascade is known to induce survival in various cells (40), the molecular mechanisms that prevent such an effect in ECs treated with PEDF constructs are not clear but may be dependent on the decline of ERK1/2 phosphorylation before JNK1/2 and p38␣ reach their peak of activity. PEDF-induced ERK1/2 phosphorylation has been previously reported by us (18) and others that linked it to the cytoprotective properties of PEDF (41,42). Indeed, our previous report showed that WT-PEDF and EEE-PEDF exhibit the same degree of neurotrophic and neuroprotective activity (18).…”
Section: Discussionmentioning
confidence: 55%
“…Modulation of MAPK signaling module by PEDF has been also suggested to play an important role in its physiological activities (44). PEDF-induced ERK1/2 phosphorylation has been largely implicated in the prosurvival effects of PEDF toward neural cells (41,42). On the other hand, the ability of PEDF to block growth of ECs and to reduce angiogenesis has been associated with up-regulation of p38 and JNK MAPKs (45,46) and p38-dependent cleavage of multiple caspases (47).…”
Section: Discussionmentioning
confidence: 99%
“…45,62,63 PEDF can protect RGC from death after glutamate toxicity, ischemia, trophic factor withdrawal, and in mouse models of glaucoma and inherited retinal degeneration. 35,38,[64][65][66][67] In vitro and in vivo, optimal RGC neuroprotective dosages of PEDF were 2.5 3 10 À5 lg/lL and 1 lg/lL, respectively. Others report that in vivo, 0.001 lg/lL is required to protect RGC from excitotoxicity and serum withdrawal, 36 a concentration of PEDF that is also neuroprotective for photoreceptors, cerebellar granule cells, and hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, Müller cells contribute to the integrity of the BRB; however, when exposed to cellular stress they impair the barrier function. Under normoxia, Müller cells secrete pigment epithelium-derived factor (PEDF), www.intechopen.com which downregulates VEGF expression and decreases vascular permeability (Yafai et al, 2007). Under hypoxia (Kaur et al, 2008) and oxidative stress ), PEDF expression is decreased in Müller cells, thus favoring the secretion of VEGF and breakdown of the inner BRB.…”
Section: Inner Blood-retinal Barriermentioning
confidence: 99%
“…The presence of ROS could also induce the expression of the vascular permeability factor VEGF in endothelial cells (Chua et al, 1998;El-Remessy et al, 2003), often associated with downstream MAPK activation (Yang et al, 2010a;Zheng et al, 2010). In Müller cells, oxidative stress leads to decreased PEDF expression , thus relieving its antagonistic effect on VEGF action and subsequent MAPK activation in endothelial cells (Yafai et al, 2007), contributing to increased vascular permeability and breakdown of the inner BRB.…”
Section: Mapk-mediated Modulation Of Intercellular Junctions In Respomentioning
confidence: 99%